2003
DOI: 10.1159/000075906
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Seeking in Young Women with Acne

Abstract: Background: It is important that acne sufferers seek medical treatment to alleviate physical and possible psychological effects as early as possible. Treatment seeking behaviour amongst acne sufferers, however, is poorly understood. Objectives: To examine which type of personality variables can predict those who will seek medical treatment. To also examine what type of help seeking is associated with better acne related quality of life. Methods: Participants were 165 female students from an Australian Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Therefore, very good correlation and agreement of subjective and objective measures might be expected. Correlation of 0.46 in our study can be compared with correlation in previous studies, [10][11][12][13][14][15][16][17][18][19][20] which has ranged from good (0.77) 14,17 to none. 11 Of more importance is the relatively poor agreement (weighted kappa of 0.35) between self-assessed and objective clinician-assessed severity.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, very good correlation and agreement of subjective and objective measures might be expected. Correlation of 0.46 in our study can be compared with correlation in previous studies, [10][11][12][13][14][15][16][17][18][19][20] which has ranged from good (0.77) 14,17 to none. 11 Of more importance is the relatively poor agreement (weighted kappa of 0.35) between self-assessed and objective clinician-assessed severity.…”
Section: Discussionsupporting
confidence: 58%
“…In previous studies, 10–20 the correlation of clinician‐assessed and patient‐assessed disease severity has ranged from very good (correlation coefficient 0.77 14,17 ) to very poor 11 but has generally been surprisingly modest. The most appropriate means of examining the relationship of subjects’ assessments and objective measures, however, is not correlation (as has been consistently utilized in previous studies) but is agreement 21 .…”
Section: Introductionmentioning
confidence: 98%
“…Studies have also indicated that the negative psychological impact of having acne is comparable to that of chronic medical conditions, including asthma, epilepsy, diabetes mellitus, back pain, and arthritis 4,10 . Despite the negative impact of acne on QOL, not all individuals with acne experience the same level of QOL impairment, indicating that other factors might be at work 11‐14 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Additionally, the use of health care by patients with skin diseases has rarely been investigated. 1,2,12 The goal of this study was to examine the prevalence of skin diseases, the use of health care by patients with skin diseases, and the relationship between this use of health care and disease-related variables (eg, disease severity and quality of life). We expected more patients with more severe skin diseases and a lower skin-related quality of life to seek more treatment.…”
Section: Introductionmentioning
confidence: 99%